Investigating Light Propagation In Full And Skimmed Milk Based On Spectroscopy And Monte Carlo Analysis - N. A. I. Muhamad Kamil; I. H. Zakaria; Wan Zakiah Wan Ismail; I. Ismail; J. Jamaludin; Sharma Rao Balakrishnan; Mus'ab Sahrim (Faculty Of Engineering, Cairo University, 2024)
Non-Indexed Publication